Human Media Values An Original and Field Study on the Jordanian Media Elites - Rababa , Muhammad; Maqableh , Rasha (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aimed to determine the extent to which the media observe human values from the perspective of the Jordanian media elites. Methods: A field questionnaire was prepared to assess these values. The descriptive approach was employed in the form of a field survey to explore the opinions of Jordanian media elites regarding the extent to which the media uphold these human values in their content. A questionnaire consisting of 77 items was prepared and distributed across five main axes. It was distributed both electronically and in person. The researchers obtained 173 responses from the media elites, which were subjected to statistical analysis using scientific research procedures. Results: IThe study revealed several findings, including the following: All legislations included high-end human principles and values, and Islam incorporates legislation and principles that emphasize these noble human values. However, it was found that the media did not consistently adhere to these standards, principles, and human values. Furthermore, statistically significant differences were observed across the study's axes due to factors such as age, the media person's affiliation with a particular medium, educational qualifications, and media experience. Conclusions: The study concluded that there is a need for an effective union to monitor the activities of media institutions and evaluate their performance in terms of their adherence to human standards and values.